Developing Learning Media on Solar Power Generation to Enhance Practical Learning of Renewable Energy Competency for Undergraduate Students in The Electrical Engineering Education Study Program - Ageed, Omer Sabri Elyas; Hariyanto, Didik; Zaid, Mustafa Suliman Khater (Jurnal Edukasi Elektro, 2026)
The increasing demand for renewable energy expertise requires practical, competency-based education, particularly in electrical engineering programs. This study aimed to address the lack of effective learning media for solar power generation, which influences student preparedness and the overall quality of renewable energy education. Using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), instructional media were developed to enhance students’ practical understanding of solar power generation. The study involved 29 sixth-semester undergraduate students enrolled in an electrical engineering education program. A quantitative approach was employed, utilizing pretests and posttests to measure learning outcomes, along with students’ feedback. The results indicated a strong need for improved solar power generation tools and revealed significant competency gaps among students. The developed media included concept maps, diagrams, case studies, and interactive exercises, received very high feasibility ratings: 91.67% from media experts, 89.57% from material experts, and 91.40% from users. Following implementation, students demonstrated a significant improvement in understanding (p = 0.012) with high test reliability (Cronbach’s Alpha = 0.891). These findings demonstrate that the developed instructional media provide a validated, and practical solution to strengthen renewable energy education and support workforce readiness for the global energy transition.